Effects of Caffeic Acid on Serum Lipid Profile and Atherogenic Index in Alloxan-Induced Diabetic Rats - Hassan Ahmadvand; Tayebeh Davoodi*; Esmaeel Babaeenezha (Lorestan University of Medical Sciences, 2017)
Background and Aim: Diabetes is a major public health problem worldwide. Oxidative stress is a risk factor in diabetes. The aim of this study is to evaluate the possible beneficial effect of caffeic acid (CA) on serum lipid parameters and atherogenic index in alloxan-induced male diabetic rats. Materials and Methods: 40 male Wistar rats were randomly divided into 4 groups: group I as the healthy control group, group II as the healthy group treated with CA (50 mg/kg i.p. daily), group III as the diabetic control group and group IV as the diabetic group treated with CA (50 mg/kg i.p.daily). Diabetes was induced in the 3rd and 4th groups by the injection of alloxan monohydrate (100 mg/kg s.c). After seven weeks, animals were anaesthetized and blood samples were collected. Then, the serum level of fasting blood glucose (FBS), lipid parameters and the atherogenic index were measured. Results: The serum level of FBS, cholesterol, low density lipoprotein (LDL-C) and atherogenic index significantly decreased in the diabetic group treated with CA compared with the untreated diabetic group. The serum level of high density lipoprotein (HDL-C) significantly increased in the treated diabetic group compared with the untreated diabetic group. Conclusion: The results of this study indicated that CA has beneficial effects on serum blood glucose, lipid profile and atherogenic index in type 1 diabetic rats.